VALUATION OF AERONAUTICS AND SPACE TECHNOLOGY AT LAPAN - Erni Br Simanjuntak; Gede Harja Wasistha (AFEBI Economic and Finance Review, 2019)
New challenges arises for government institutions engaged in research and engineering to continuously innovate and develop technologies that have competitive advantages and provide income for the country through royalty from licensed technology. This research carried out to valuate the aeronautics and space technology. The objective of the study is to develop appropriate intellectual property valuation methods. This research is a case study utilizing sequential mix method which is the combination of quantitative and qualitative research. By using intellectual capital theory, this research-broaden the literatures on the technology valuation in the field of aeronautics and space. This study fills research gap on the existing technology valuation method that is still partially conducted by government research and development. This study discusses the value of intangible assets and licenses from intellectual property that are calculated through three valuation approaches, such as cost-based approach, income-based approach, and market-based approach. The results of the study show that the most appropriate intellectual property valuation method are the cost-based approach and income-based approach.JEL Classification: O30, O31, O33Keywords: Cost Based Approach, Income Based Approach, Intellectual Property, Market Based Approach, Sequential Mix Method